2019
DOI: 10.1101/797308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The PMK-3 (p38) Mitochondrial Retrograde Response Functions in Intestinal Cells to Extend Life via the ESCRT Machinery

Abstract: The p38 mitogen-activated protein kinase (MAPK) PMK-3 controls a life-extending retrograde response in the nematode Caenorhabditis elegans that is activated following mitochondrial electron transport chain (ETC) disruption and is distinct from known longevity-promoting pathways. Here we show that the long isoform of PMK-3 expressed exclusively in the gut, rather than neurons, is sufficient to fully extend the life of animals exposed to mild ETC dysfunction. Surprisingly, constitutive activation of PMK-3 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Our findings emphasize that caution must be used in interpreting previous tissue-specific RNAi studies using the rde-1(ne219) and rrf-1 strains. Similarly, researchers should also be aware that the tissue-specific promotors may also exhibit a low level of expression in other tissues, as was observed in this study (Radetskaya et al 2019). Transgenic approaches manipulating CRISPR-Cas9 activity in a tissue-specific manner (Shen et al 2014) or using conditional protein degradation methods may be more precise approaches for tissue-specific knockdown experiments in C. elegans (Nance and Frokjaer-Jensen 2019).…”
Section: Discussionmentioning
confidence: 60%
“…Our findings emphasize that caution must be used in interpreting previous tissue-specific RNAi studies using the rde-1(ne219) and rrf-1 strains. Similarly, researchers should also be aware that the tissue-specific promotors may also exhibit a low level of expression in other tissues, as was observed in this study (Radetskaya et al 2019). Transgenic approaches manipulating CRISPR-Cas9 activity in a tissue-specific manner (Shen et al 2014) or using conditional protein degradation methods may be more precise approaches for tissue-specific knockdown experiments in C. elegans (Nance and Frokjaer-Jensen 2019).…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, p38c is known to have a dual functionality: it participates in the stress response typical to p38 group and has a novel function in lipid metabolism [25]. PMK-3 from C. elegans is another paralog with a long branch, and it was shown to be a part of a novel mechanism of survival [26,27]. In this study, we found five more examples of highly diverged p38 paralogs in invertebrates (table 1).…”
Section: Resultsmentioning
confidence: 65%
“…Since deletion of either zip-2 or pmk-3 significantly reduced the lifespan of lonp-1 mutants, we speculate that this novel crosstalk between MAPK mt and ZIP-2 is important in modulating the ageing process under mitochondrial dysfunction. This is strengthened by the observation that the DLK-1/PMK-3 signaling pathway declines with age, and this is overcome by mild mitochondrial stress [62]. Future studies investigating the underlying molecular mechanism and transcriptional targets are expected to shed light on the relevant ageing modulators.…”
Section: Discussionmentioning
confidence: 94%